Performance analysis of solar energy integrated with natural-gas-to-methanol process. (15th October 2017) - Yang, Sheng; Liu, Zhiqiang; Tang, Zhiyong; Wang, Yifan; Chen, Qianqian; Sun, Yuhan
Highlights: Solar energy integrated with natural-gas-to-methanol process is proposed. The two processes are modeled and simulated. Performance analysis of the two processes are conducted. The proposed process can cut down the greenhouse gas emission. The proposed process can save natural gas consumption. Abstract: Methanol is an important platform chemical. Methanol production using natural gas as raw material has short processing route and well developed equipment and technology. However, natural gas reserves are not large in China. Solar energy power generation system integrated with natural-gas-to-methanol (NGTM) process is developed, which may provide a technical routine for methanol production in the future. The solar energy power generation produces electricity for reforming unit and system consumption in solar energy integrated natural-gas-to-methanol system (SGTM). Performance analysis of conventional natural-gas-to-methanol process and solar energy integrated with natural-gas-to-methanol process are presented based on simulation results. Performance analysis was conducted considering carbon efficiency, production cost, solar energy price, natural gas price, and carbon tax. Results indicate that solar energy integrated with natural-gas-to-methanol process is able to cut down the greenhouse gas (GHG) emission. In addition, solar energy can replace natural gas as fuel. This can reduce the consumption of natural gas, which equals to 9.2% of the total consumed natural gas. However, it is not economical considering the current technology readiness level, compared with conventional natural-gas-to-methanol process.